THE EVOLUTION OF FIRM SIZE DISTRIBUTION - KITOV, Ivan O. (Theoretical and Practical Research in Economic Fields; Vol 2 No 1 (2011): TPREF, Volume II, Issue 1(3), Summer 2011, 2011)
Significant differences in the evolution of firm size distribution for various industries in the United States have been revealed and documented. For theoretical considerations, this finding puts major constraints on the modelling of firm growth. For practical purposes, the observed differences create a solid basis for selective investment strategies.